Narrow Linewidth and Temperature Insensitive Blue Phase Liquid Crystal Films - Xiao Wan Xu; Yan Jun Liu; Fei Wang; Dan Luo (IEEE Photonics Journal, 2018)
Blue phase liquid crystal films are quite useful in reflective displays, flexible photonic devices, and optical sensors. However, the effects of refractive index properties of refilled liquid crystals and environment temperature on reflection properties of blue phase liquid crystal films are far from fully exploration. Herein, we demonstrate blue phase liquid crystal films refilled with different nematic liquid crystals. The effects of birefringence and average refractive index of refilled nematic liquid crystals on the reflection properties such as reflectance, central wavelength, and linewidth of photonic band have been studies. The temperature effect on reflectance and central wavelength has been studied. A narrow linewidth (19.4 nm) and temperature insensitivity blue phase liquid crystal film has been fabricated by refilling liquid crystals of DYX8013 with small birefringence. The narrow linewidth and excellent temperature insensitivity properties of BPLC film can be applied in color reflective display and flexible photonic devices.